2011
DOI: 10.1002/eat.20811
|View full text |Cite
|
Sign up to set email alerts
|

The 5‐HTTLPR polymorphism and eating disorders: A meta‐analysis

Abstract: To be carrier of the 5-HTTLPR S allele seem to represent a risk factor for eating disorders, especially for AN. However, considering the reported high between-study heterogeneity, future studies should focus on more homogeneous endophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 44 publications
2
54
3
3
Order By: Relevance
“…Furthermore, two single-nucleotide polymorphisms (SNPs) within 5-HTTLPR, rs25531 and rs25532, have been found to affect transcriptional activity (Murphy and Lesch, 2008). In accordance with findings in the SERT-KO mice, the low-expressing s allele of the 5-HTTLPR has been associated with anxiety-related personality traits Holmes et al, 2003b) and neuropsychiatric conditions such as bipolar disorder (Cho et al, 2005;Lasky-Su et al, 2005), autism (Huang and Santangelo, 2008), obsessive-compulsive disorder (OCD) (Lin, 2007), 610 KRISTENSEN ET AL. eating disorders (Calati et al, 2011), major depressive disorder (Clarke et al, 2010;Kiyohara and Yoshimasu, 2010), and predisposition to develop depression in response to stressful life events (Caspi et al, 2003). However, two recent meta-analyses have failed to support a correlation among 5-HTTLPR, stress, and depression (Munafò et al, 2009;Risch et al, 2009), and this geneby-environment interaction is still the subject of debate (Risch et al, 2009;Wankerl et al, 2010).…”
Section: B the Serotonin Transportermentioning
confidence: 99%
“…Furthermore, two single-nucleotide polymorphisms (SNPs) within 5-HTTLPR, rs25531 and rs25532, have been found to affect transcriptional activity (Murphy and Lesch, 2008). In accordance with findings in the SERT-KO mice, the low-expressing s allele of the 5-HTTLPR has been associated with anxiety-related personality traits Holmes et al, 2003b) and neuropsychiatric conditions such as bipolar disorder (Cho et al, 2005;Lasky-Su et al, 2005), autism (Huang and Santangelo, 2008), obsessive-compulsive disorder (OCD) (Lin, 2007), 610 KRISTENSEN ET AL. eating disorders (Calati et al, 2011), major depressive disorder (Clarke et al, 2010;Kiyohara and Yoshimasu, 2010), and predisposition to develop depression in response to stressful life events (Caspi et al, 2003). However, two recent meta-analyses have failed to support a correlation among 5-HTTLPR, stress, and depression (Munafò et al, 2009;Risch et al, 2009), and this geneby-environment interaction is still the subject of debate (Risch et al, 2009;Wankerl et al, 2010).…”
Section: B the Serotonin Transportermentioning
confidence: 99%
“…In a recent study, Crujeira et al [76] found that NPY and POMC methylation levels reflect a putative epigenetic regulation implicated in the weight regain process. Also, the promoter region hypermethylation of the serotonin transporter gene ( SLC6A4), previously related with eating disorders and body weight [77,78], was associated with an increase in BMI, body weight and waist circumference [79].…”
Section: Some Studies On Dna Methylation By Tissue Specificitymentioning
confidence: 97%
“…На выборке из 71 женщи-ны с ВЕD с ожирением и без такового (в группе контро-ля с нормальным весом была 61 женщина) показано, что не S-, а L-аллель 5-HTTLPR увеличивает риск раз-вития ВЕD [37]. Согласно результатам метаанализов, S-аллель 5-HTTLPR может являться фактором риска развития расстройств пищевого поведения в целом [38], особенно анорексии [28], для которой получены наи-лучшие показатели достоверности [39]. Однако доказа-тельств влияния на риск развития ВЕD до сих пор нет.…”
Section: молекулярная генетика веDunclassified